Peran Komunikasi Keluarga Terhadap Perilaku Anak (Studi Tentang Perubahan Perilaku Transgender) THE ROLE OF FAMILY COMMUNICATIONS TOWARD CHILDREN BEHAVIOR (STUDY ABOUT TRANSGENDER BEHAVIOR CHANGES - Siska Armawati Sufa (Inter Komunika, 2021)
In feminism's perception, gender is only a product of culture (nature), that is, only the "perception" of the Society or even a myth for what is called the patent (natural) attitude of men and women. Interchangeable and non-permanent genders can be changed with some of the paradigms of thinking that form the basis of the culture of society. The pattern of family communication is very important in the acceptance and delivery that occurs between family members. How parents apply parenting patterns in the family will make the self-concept of their children. How individuals seek themselves is called self-concept.This study aims to: (1) Learning individual communication in the formation of individual gender identity (2) Knowing the communication patterns of transgender members (3) Knowing patterns of family communication in transgender individuals. Several institutions in this study; (1). Open and appropriate communication for transgender individual families has self-construction with a gender role. So that the family and the social environment are able to provide the correct gender understanding and provide a variety of gender assignments are correct. (2) The inaccessible family communication of transgender individuals has self-construction with two gender stages. Dramaturgy on the frontstage of the true gender role will be released in the family environment, backstage will be displayed outside the family circle. (3) A linear and unusable pattern of communication in transgender individuals has many masks. Dramaturgy on the frontstage is enhanced on the video lot will be more difficult to correct the actual gender game. Keywords: transgender, self-construction, family communication